Crisis Communication through Social Media Platforms by Malaysian Indian Agencies - Perumal, Thanalachime; Sinayah, Malarvizhi; N Govaichelvan, Kumanan; Shanmuganathan, Thilagavathi; Gan, Yee Chin (Jurnal Arbitrer, 2024)
Crisis communication must be prompt, accurate, and accessible to all. Government agencies often use multiple channels to disseminate critical information quickly. Social media has been helpful in informing all stakeholders about institutional short- and long-term interests as well as raising public health awareness. Mitigative strategies and crisis response are improved when crisis communication is tailored to the social, cultural, and economic context of minority communities. Identifying and directing communications that are unique to a group, however, presents difficulties when a crisis arises. Therefore, this research aims to investigate how the Malaysian Indian Agencies (MIAs), use social media to reach out to minority Malaysian Indians to disseminate information during the COVID-19 pandemic. 16 MIAs with active social media pages, Facebook and Twitter, registered with the Registrar of Societies (ROS) were shortlisted. Content analysis was performed on social media posts which were published from 18 March 2020 until 31 August 2020. The posts were categorized based on crisis communication strategies, outlined based on past studies. Subsequently, a semi-structured interview was conducted among the urban middle class and urban poor Indian residents in the Klang Valley. Findings reveal a notable paucity in the proactive presence of these agencies on social media platforms, indicating limited engagement in disseminating essential information during a crisis. While Facebook and Twitter were used, diverse channels like WhatsApp contributed to reaching out to the non-urban Indians. The use of Tamil shows efforts to overcome language barriers, supporting government initiatives to control the pandemic while potentially boosting the agencies’ political influence among Tamil-speaking communities. This study underscores the need for government agencies and community organizations to adapt their outreach methods to ensure all segments of the population, especially linguistic minorities, have access to timely and accurate information during a crisis.